2017
DOI: 10.17269/cjph.108.6068
|View full text |Cite
|
Sign up to set email alerts
|

Active living in Saskatchewan: A review of official community plans

Abstract: OBJECTIVE: Municipal policies may have a significant impact on the development of environments that provide sustainable opportunities for individuals to engage in healthy, active lifestyles. Little is known about how explicitly community planning in Canada integrates strategies to promote physical activity. In the context of Active Saskatchewan 2020 (AS2020), the strategic plan of Saskatchewan in motion, such an analysis would create a basis for identifying policy gaps and ongoing monitoring. The objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Almost all PA strategies included the indicator ‘offer play spaces with loose parts, natural elements, and pop-up adventure activities’ by describing actions related to ‘try-it’ days or drop-in sessions for activities like snow shoeing, hiking, or kayaking. A study that reviewed PA-related policies in Saskatchewan community plans reported policies related to residential neighborhood plans, cycling and pedestrian plans, and joint-use agreements between communities and schools were most common [ 11 ]. Similarly, actions related to ‘Safe and active routes around the community’ were reported in all but one PA strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all PA strategies included the indicator ‘offer play spaces with loose parts, natural elements, and pop-up adventure activities’ by describing actions related to ‘try-it’ days or drop-in sessions for activities like snow shoeing, hiking, or kayaking. A study that reviewed PA-related policies in Saskatchewan community plans reported policies related to residential neighborhood plans, cycling and pedestrian plans, and joint-use agreements between communities and schools were most common [ 11 ]. Similarly, actions related to ‘Safe and active routes around the community’ were reported in all but one PA strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this framework has not yet been applied to the analysis of municipal PA or AT strategies or plans in Canada. A previous study in Saskatchewan, Canada reviewed official community plans or policies supportive of PA in 17 cities and found that the most common policies were related to residential neighborhood plans, downtown cycling and pedestrian plans, plans to improve active recreation, joint-use agreement between community and schools, school travel plans, and AT plans [ 11 ]. Except for those associated with school travel plans and AT, the indicators included in the Saskatchewan official community plans were not reflective of the actions included in the Play-Friendly Cities framework.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al's (2017) study explores the inclusion of physical activity (and physical activity-related) supportive policies in Official Community Plans (equivalent to OPs) in Saskatchewan cities with a population of 4,500+ people. The study finds that Official Community Plans lack policy support for physical activity and there is opportunity to improve plans in the future (Hassan et al, 2017). The limited research (based on this sample of work) about older adults and walkable environments reveals an opportunity to explore this MRP topic further using a plan quality evaluation methodology.…”
Section: )mentioning
confidence: 92%
“…Articles from this search were combined with an additional article the author found in a previous, non-plan evaluation related search, as well as an article passed along from the author's supervisor. Within a sample of acquired work 1 spanning over the last 20 years, only one study assessed plans with an exclusive focus on older adults (Krawchenko et al, 2016), and only one study assessed plans with a focus on physical activity (including walking; Hassan et al, 2017), exclusively in a Canadian context. Krawchenko et al (2016) study the connection between agefriendly communities and place and social vulnerability, as it relates to climate change, in rural communities in Nova Scotia.…”
Section: )mentioning
confidence: 99%
“…The sample of work from the author's search and from previously acquired articles included 21 articles(Benelli & Magaudda, 2017;Bittner et al, 2013;Campbell, 2009;Dedekorkut et al, 2010;Edwards & Haines, 2007;Gough, 2015;Guyadeen et al, 2019;Harris et al, 2019;Hassan et al, 2017;Hausman & Becker, 2000;Kim & Kakimoto, 2014;Krawchenko et al, 2016;Luo & Qi, 2019;Manaugh et al, 2015;Muhlbach, 2012;Park et al, 2020;Price et al, 2018;Raparthi, 2015;Ren et al, 2008;Seasons, 2002;Xu & Yang, 2019).…”
mentioning
confidence: 99%